PENGENDALIAN CYBERBULLLYING DAN HOAX MELALUI PELATIHAN TERBIMBING DI SMK NEGERI 2 TEBING TINGGI - Alexander, Irving Josafat (Sinesia : Jurnal Pengabdian Masyarakat, 2025)
The rapid development of information technology has brought both positive and negative impacts on daily life. One of the negative impacts that has become a concern is the increasing prevalence of cyberbullying and the spread of hoaxes among students. As an educational institution, SMK Negeri 2 Tebing Tinggi plays an important role in equipping students with good digital literacy to ensure they use technology wisely. This study aims to analyze the effectiveness of guided training in enhancing students' understanding of the dangers of cyberbullying and hoaxes, as well as strategies to control them. The method used is a qualitative approach involving observation, interviews, and evaluations conducted before and after the training. The results of the study show that the training significantly increased students' awareness and understanding of how to recognize and prevent cyberbullying and hoaxes. Moreover, the training also helped students develop critical thinking skills and digital ethics. Therefore, guided training proves to be an effective strategy in fostering a healthy digital culture within the school environment.